P2 Receptors as Therapeutic Targets in the Salivary Gland: From Physiology to Dysfunction - Khalafalla, Mahmoud G.; Woods, Lucas T.; Jasmer, Kimberly J.; Forti, Kevin Muñoz; Camden, Jean M.; Jensen, Janicke L.; Limesand, Kirsten H.; Galtung, Hilde K.; Weisman, Gary A. (Frontiers in Pharmacology, 2020)
Although often overlooked in our daily lives, saliva performs a host of necessary physiological functions, including lubricating and protecting the oral cavity, facilitating taste sensation and digestion and maintaining tooth enamel. Therefore, salivary gland dysfunction and hyposalivation, often resulting from pathogenesis of the autoimmune disease Sjögren’s syndrome or from radiotherapy of the head and neck region during cancer treatment, severely reduce the quality of life of afflicted patients and can lead to dental caries, periodontitis, digestive disorders, loss of taste and difficulty speaking. Since their initial discovery in the 1970’s, P2 purinergic receptors for extracellular nucleotides, including ATP-gated ion channel P2X and G protein-coupled P2Y receptors, have been shown to mediate physiological processes in numerous tissues, including the salivary glands where P2 receptors represent a link between canonical and non-canonical saliva secretion. Additionally, extracellular nucleotides released during periods of cellular stress and inflammation act as a tissue alarmin to coordinate immunological and tissue repair responses through P2 receptor activation. Accordingly, P2 receptors have gained widespread clinical interest with agonists and antagonists either currently undergoing clinical trials or already approved for human use. Here, we review the contributions of P2 receptors to salivary gland function and describe their role in salivary gland dysfunction. We further consider their potential as therapeutic targets to promote physiological saliva flow, prevent salivary gland inflammation and enhance tissue regeneration.